Electrochemical measurements used for assessment of corrosion and protection of metallic materials in the field: A critical review - Xia, Da Hai; Deng, Cheng Man; Macdonald, Digby; Jamali, Sina; Mills, Douglas; Luo, Jing Li; Strebl, Michael; Amiri, Mehdi; Jin, Weixian; Song, Shizhe; Hu, Wenbin (Journal of Materials Science & Technology, 2022)
Corrosion degradation is detrimental to metal structures as it shortens their lifetime and leads to huge economic losses and unexpected disasters. Therefore, the detection and monitoring of corrosion degradation is of great importance. Herein, we briefly review the state-of-the-art electrochemical methods, instrumentation (based on virtual instrumentation), and advanced sensor/probes that are used in the field for the assessment of corrosion damage. Typical corrosion monitoring results, some of which have been obtained at Tianjin University in the past 30 years, for metallic materials and organic coating/metal systems in atmospheric, marine, and soil conditions in the field are presented. Detection methods, data analysis, and theoretical and mathematical models regarding each corrosion system are discussed, and the challenges, problems and possible solutions for each case are suggested. Lastly, future developments, such as wireless, intelligent, and automatic electrochemical measurement, that will augment the present electrochemical methods of evaluating corrosion degradation are summarized.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Corrosion monitoring; Data analysis; Electrochemical method; In-situ measurement; Probe; Sensor; Virtual instrumentation